Revitalisering van het mijnverleden in Heerlen door hybride taalculturele praktijken - Cornips, Leonie; van den Hengel, Louis (Studies over de sociaaleconomische geschiedenis van Limburg, 2018)
Revitalisation of Heerlen’s coal mining past through languagecultural practices This paper examines how inhabitants of Heerlen relate to the coal mining past of this city through a variety of languagecultural practices that cut across diverse media forms and genres, both textual (poems, rap songs), visual (portrait photography, material commodities), and digital (posts on Facebook, YouTube videos). Through these practices people in Heerlen express, repeat, and renew their individual and collective memories of Heerlen as the centre of the former Eastern Mining District in the twentieth century. We argue that Heerlen is undergoing a process of revitalisation that creates social personae, embedded locally, which are labelled tuupisch (typical). From a normative perspective, performances of identity and memory attributed and/or imagined as linked to this tuup (type) are often parodic and hybrid in character. Through an analysis of various examples, the paper demonstrates the critical potential of such hybrid languagecultural practices to contest dominant perspectives on the city’s mining heritage, to renegotiate place-based identities, and to establish new forms of cultural memory